Narasi Deradikalisasi di Media Online Republika dan Arrahmah - Zainal Fikri (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2013)
By using a semiotic approach, this study explored deradicalization narrative in the two online Islamic media, Republika and Arrahmah. This study aimed at clarifying the meanings of deradicalization in Indonesia and contributing to the implementation of deradicalization project. The study was conducted by using a textual analysis, mainly paradigmatic and syntagmatic analysis. This study found Republika narrated that the deradicalization was the efforts to prevent radical ideology and to correct misinterpretation towards Islam. For Arrahmah , deradicalization was a part of war against Islam and distorted the teachings of Islam. Keywords: Semiotics, Deradicalization, Terrorism, Jihad.